Effectiveness of The Active Cycle Breathing Technique on The Peak Expiratory Flow Rate (PEFR) in Asthma Patient - Julvainda Eka Priya Utama (Babali Nursing Research, 2020)
Introduction: The Peak Expiratory Flow Rate (PEFR) is a person maximum expiratory airflow measurement. The active cycle breathing technique is a breathing exercise focus on release the abnormal lung secretion by increase the expiration power. The aim of this study was to analyze the effectiveness of the active cycle breathing technique on the PEFR in asthma patient. Methods: Design of this study was quasi-experimental with single pre-post test group. Study was conducted in the Kedungkandang Primary Health Care, Malang City, East Java Province, Indonesia. In total 25 asthma patients recruited into a single group. The participant asked to practice the breathing exercise for three times a week and being evaluated after one month. The PEFR was measured by Peak Flow Meter. Results: The Wilcoxon test showed p grade < 0.05, which means there is a significant effect of the active cycle breathing technique on the PEFR grade. The increase of PEFR grade in asthma patients start to appear at the week third to the end of week fourth. Continuous treatment may increase the PEFR grade, however it was influenced by several factors such as age (years) and educational background. Conclusion: The active cycle breathing technique increase PEFR in asthma patients. The PEFR expected to be evaluated simultaneously, to assess the stages of improvement for asthma patient.